Dormancy - Withers, P. C.; Cooper, Christine (Elsevier, 2008)
Dormancy or torpor is a widely-recognized behavioral and physiological state of bothanimals and plants that generally indicates inactivity and reduced metabolic rate. It caninvolve very different physiological states in response to a variety of environmentalstimuli, including temperature, water, or food. It can last < 1 day, may occur for a fewconsecutive days, or may last an entire season or even many years. Torpor involvesphysiological changes related especially to body temperature, metabolism and waterbalance. Hibernation is when an organism spends the winter in a state of dormancy; it islong-term multi-day torpor for survival of cold conditions. Estivation is summer dormancy, for survival of hot and dry periods. The general roles of torpor, hibernation or estivation are avoidance of unfavorable or lethal short- or long-term (seasonal) climatic conditions and conservation of energy during this period of inactivity. Seasonaldormancy allows species to exploit ephemeral environments and colonize habitats that would otherwise be unsuitable for growth or survival at certain times of the year. Thereare costs to dormancy and torpor, but the advantages contribute to the fitness of individuals and species that use it.